SAT0510 Painful Shoulder: Relevance of Clinical and Sonographic Data on Corticosteroid Injection Outcome. (15th July 2016) - Cerqueira, M.; Sousa Neves, J.; Santos Faria, D.; Teixeira, F.; Afonso, M.C.; Costa, J.A.
Abstract : Background: Painful shoulder (PS) is a common condition and a frequent cause of referral to a Rheumatology department, particularly in refractory patients. Objectives: To study the association between clinical and sonographic data and corticosteroid injection (CI) outcome in PS patients. Methods: Adult patients with PS, consecutively observed in a Rheumatology outpatient clinic were included. Demographic and clinical data (age, gender, time of symptoms, pain in contralateral shoulder, past CI of any shoulder, active abduction limitation and dominant side) were registered. The portuguese version of QuickDASH questionnaire (QD) and pain Visual Analogic Scale (VAS) were answered by the patient. If the patient fulfilled clinical criteria for CI (inflammatory or mixed pattern of pain, refractory to at least a 2 week NSAID treatment on full dose, or contra-indication to NSAID, and absence of contraindication to CI), a shoulder ultrasound (US) was performed before CI, and the sonographic findings were registered (presence of subacromial bursitis (SAB), long bicipital head tenosynovitis (LBHT), tendon calcification or supraspinatus (SS) tear). After 9 ± 2 weeks, patients were reassessed, repeating the QD and VAS questionnaires. Absolute and relative variation of QD score (aΔQD and rΔQD, respectively) and absolute and relative variation of pain VAS (aΔVAS and rΔVAS, respectively) were calculated. Patients with generalized pain syndromes, with suspected or confirmed chronic rheumatic inflammatory disease or secondary cause of the shoulder pain, with sonographic complete supraspinatus tear or glenoumeral effusion and those refusing CI treatment or proposed for calcification lavage, or those in whom reassessment was out of the defined interval were excluded. Statistical analysis was performed using SPSS 21.0 software. Results: Sixty-eight patients were included, of whom 36 were excluded because of presenting at least one of the exclusion criteria. Thirty-two patients, 23 women, with a mean age of 58.9 ± 10.2 years, concluded the study. The mean time of symptoms was 8 ± 7.4 months; 11 (34.4%) patients had also pain in the contralateral shoulder, 8 (25%) had active abduction limitation, 5 (15.6%) had history of shoulder CI, and 24 (75%) had pain on the dominant side. Regarding US findings, 18 (56.3%) had SAB, 12 (37.5%) had LBHT, 16 (50%) had intratendinosis or transtendinosis SS tear and 11 (34.4%) had any tendon calcification. Age or time of symptoms did not correlate with any of the improvement scores. Higher baseline QD score correlated with higher aΔQD ( r =0.55, p <0.01) and rΔQD ( r =0.37, p <0.05); higher baseline VAS score correlated with higher aΔVAS ( r =0.38, p <0.05). SS tear was present in older patients ( p <0.05), but it was not associated to improvement scores. Active abduction limitation was associated with greater aΔQD or rΔQD ( p <0.01), and aΔVAS or rΔVAS ( p <0.05). Patients with sonographic inflammatory signs (SAB or LBHT) had greater aΔVAS and rΔVAS scores ( p <0.05); there was also a trend towards greater improvement on QD scores, although not statistically significant. Conclusions: Patients with more severe symptoms or active abduction limitation have greater benefit from CI; having any of the inflammatory US findings described is also associated with greater pain relief after CI. Disclosure of Interest: None declared